"Take home" naloxone: what does the evidence base tell us?. Issue 2 (1st June 2015) - Breedvelt, Josefien J. F.; Tracy, Derek K.; Dickenson, Emily C.; Dean, Lucy V.
Abstract : Purpose: – Opiod users are at high risk of suffering from drug overdoses. Naloxone has been used for decades in emergency treatment settings to reverse the symptoms of opioid overdose. Pilot studies and regional programmes have been rolled out to make naloxone more widely available. This review of user/carer administration of naloxone – so-called "take home naloxone" – aims to provide health professionals and interested readers with an up-to-date evidence base, clinical implications and practical concern considerations for such community management. The paper aims to discuss these issues. Design/methodology/approach: – A review and analysis of the recent literature on naloxone. Findings: – The evidence base suggests training and education is effective in preparing users for wider naloxone distribution. Furthermore, studies of varying quality indicate that naloxone may prove useful in reducing overdose-related deaths. However, even after implementation ineffective response techniques continued to be used at times and there remained a heistance to call medical services post overdose. Intranasal naloxone may reduce some of the risks associated with intramuscular naloxone. Ethical considerations, including provision of a needle and syringe kit to the community, should be considered. Studies suffered from a lack of follow-up data and methodological difficulties are associated with establishing opioid-related deaths post implementation. Two running trials in the UK might mitigate these concerns. Research limitations/implications: – Future research is needed to address wider context of an overdose and targeting associated risk factors. Originality/value: – Clinicians and other professionals will be informed on the most up-to-date evidence base and which areas are improtant to consider when take-home naloxone is introduced in their services.